Strength, Jumping, and Change of Direction Speed Asymmetries Are Not Associated With Athletic Performance in Elite Academy Soccer Players - Raya-González, Javier; Bishop, Chris; Gómez-Piqueras, Pedro; Veiga, Santiago; Viejo-Romero, David; Navandar, Archit (Frontiers in Psychology, 2020)
The aims of the present study were twofold: 1) to measure inter-limb asymmetries from a battery of fitness tests in youth soccer players and, 2) determine the association between asymmetry and measures of athletic performance. Sixteen elite youth soccer players (14.7±0.2 years) performed a single leg Abalakov test (ABK), change of direction (COD) test over 10m (5+5) and 20m (10+10), and an iso-inertial power test. Subjects also performed 10m, 20m and 30m sprints and a double leg countermovement jump (CMJ, which were correlated with all ABK, COD and iso-inertial asymmetry scores. A one-way repeated measures ANOVA showed significant differences between inter-limb asymmetry scores across multiple tests (p < 0.05), with the iso-inertial power test presenting the greatest magnitude of asymmetry, while individual data highlighted substantially greater inter-individual differences in each test. Spearman's rank order r correlations showed no significant relationships (p > 0.05) between the different inter-limb asymmetry scores, and between asymmetry scores and athletic performance. These results show the test-specific nature of asymmetries in youth soccer populations, suggesting the necessity of perform a fitness test battery to provide a specific information of the asymmetries in the soccer players, being adequate to analyze individually these data. In addition, several strategies should be considered to improve the performance in youth soccer players.